NATIONAL CHARACTERISTICS IN MUSIC (Lad, Harmony, Texture) (Neo Science Peer Reviewed Journal, 2023)
In this article, the composition of musical works of composers and composers is a combination of sounds, rhythm and tones, the structure of musical tones affecting the human psyche in the essence of the work, the arrival of folk tones in the melody, and the achievement of nationalism in music. The information about the overture "Ceremony" by the composer Sulaymon Yudakov shows national melodies.